Effects of Surgical vs. Nonsurgical Therapy on Erectile Dysfunction and Quality of Life in Obstructive Sleep Apnea Syndrome: A Pilot Study. (27th March 2013) - Shin, Hyun‐Woo; Park, Ju‐Hyun; Park, Jong‐Wan; Rhee, Chae‐Seo; Lee, Chul Hee; Min, Yang‐Gi; Kim, Dong‐Young
Abstract: Introduction: Obstructive sleep apnea syndrome (OSAS) is associated with erectile dysfunction (ED). The improvement of ED after medical therapy including continuous positive airway pressure (CPAP) or mandibular advancement devices (MADs) is still controversial. Furthermore, the efficacy of surgical treatment has been little investigated. Aim: The aim of this nonrandomized prospective study was to evaluate the effects of surgical (uvulopalatopharyngoplasty [UPPP]) and nonsurgical approaches (CPAP and MAD) on ED and quality of life (QOL) in OSAS. Methods: OSAS patients underwent UPPP (N = 30), CPAP (N = 16), or MAD (N = 10) and completed the Korean versions of the International Index of Erectile Function questionnaire (KIIEF‐5) and the Calgary Sleep Apnea Quality of Life Index (SAQLI) before and after a median of 7 months of treatment (interquartile range, 4–15 months). All patients underwent a full‐night in‐laboratory polysomnography at baseline and follow‐up. Main Outcome Measure: The main outcome measures are the KIIEF‐5 and SAQLI scores. Results: CPAP group showed older age, higher body mass index, and more severe OSAS than other groups. Apnea–hypopnea index and lowest oxygen saturation level improved significantly in all groups, but Epworth Sleepiness Scale score decreased significantly in UPPP and MAD groups. Significant increase of KIIEF‐5 was observed in patients who underwent UPPP ( P = 0.039, paired t ‐test), but not in nonsurgical treatment group. All groups had the tendency of better QOL after treatment, but statistical significance was found only in MAD group. Neck circumference ( r = 0.360, P = 0.006) and KIIEF‐5 score ( r = −0.484, P < 0.001) at baseline were significantly related to the improvement of KIIEF‐5. Conclusions: This study demonstrated that ED in OSAS may improve following UPPP. Better disease‐specific QOL was observed after both surgical and nonsurgical therapies in OSAS. These findings suggest that interventions for OSAS can provide the alleviation of ED and increase QOL in OSAS patients with ED, especially if they had pronounced complaints of ED and wide neck circumferences.Shin H‐W, Park J‐H, Park J‐W, Rhee C‐S, Lee CH, Min Y‐G, and Kim D‐Y. Effects of surgical vs. nonsurgical therapy on erectile dysfunction and quality of life in obstructive sleep apnea syndrome: A pilot study. J Sex Med 2013;10:2053‐2059.